Long-Term Effect of Decompressive Craniectomy on Intracranial Pressure and Possible Implications for Intracranial Fluid Movements. Issue 2 (15th February 2019) - Lilja-Cyron, Alexander; Andresen, Morten; Kelsen, Jesper; Andreasen, Trine Hjorslev; Fugleholm, Kåre; Juhler, Marianne
Abstract: BACKGROUND: Decompressive craniectomy (DC) is used in cases of severe intracranial hypertension or impending intracranial herniation. DC effectively lowers intracranial pressure (ICP) but carries a risk of severe complications related to abnormal ICP and/or cerebrospinal fluid (CSF) circulation, eg, hygroma formation, hydrocephalus, and "syndrome of the trephined." OBJECTIVE: To study the long-term effect of DC on ICP, postural ICP regulation, and intracranial pulse wave amplitude (PWA). METHODS: Prospective observational study including patients undergoing DC during a 12-mo period. Telemetric ICP sensors (Neurovent-P-tel; Raumedic, Helmbrechts, Germany) were implanted in all patients. Following discharge from the neuro intensive care unit (NICU), scheduled weekly ICP monitoring sessions were performed during the rehabilitation phase. RESULTS: A total of 16 patients (traumatic brain injury: 7, stroke: 9) were included (median age: 55 yr, range: 19-71 yr). Median time from NICU discharge to cranioplasty was 48 d (range: 16-98 d) and during this period, mean ICP gradually decreased from 7.8 ± 2.0 mm Hg to –1.8 ± 3.3 mm Hg ( P = .02). The most pronounced decrease occurred during the first month. Normal postural ICP change was abolished after DC for the entire follow-up period, ie, there was no difference between ICP in supine and sitting position ( P = .67). PWA was markedly reduced and decreased from initially 1.2 ± 0.7 mm Hg to 0.4 ± 0.3 mm Hg ( P = .05). CONCLUSION: Following NICU discharge, ICP decreases to negative values within 4 wk, normal postural ICP regulation is lost and intracranial PWA is diminished significantly. These abnormalities might have implications for intracranial fluid movements (eg, CSF and/or glymphatic flow) following DC and warrants further investigations. Graphical Abstract: